2019
DOI: 10.1038/s41598-019-43967-0
|View full text |Cite
|
Sign up to set email alerts
|

Further observations on a principal components analysis of head-related transfer functions

Abstract: Humans can externalise and localise sound-sources in three-dimensional (3D) space because approaching sound waves interact with the head and external ears, adding auditory cues by (de-)emphasising the level in different frequency bands depending on the direction of arrival. While virtual audio systems reproduce these acoustic filtering effects with signal processing, huge memory-storage capacity would be needed to cater for many listeners because the filters are as unique as the shape of each person’s head and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Mokhtari et al [318] extended the study in [323] and performed another PCA investigation and a discrete cosine transform of HRTF magnitudes by employing FDTD (∆X = 2 mm) simulations coupled with a near-to-far integral approximation for 38 ears acquired from 19 adults.…”
mentioning
confidence: 99%
“…Mokhtari et al [318] extended the study in [323] and performed another PCA investigation and a discrete cosine transform of HRTF magnitudes by employing FDTD (∆X = 2 mm) simulations coupled with a near-to-far integral approximation for 38 ears acquired from 19 adults.…”
mentioning
confidence: 99%
“…Traditionally, principal component analysis (PCA) has been the technique of choice for dimensionality reduction in HRTF datasets, leading to many interesting observations and experiments that evaluate the impact of different eigenmodes on spatial audio perception [188]. Further improvements in PCA-based HRTF modeling and customization were presented in [189,190]. HRTFs were synthesized in [191] using a sparse combination of a subject's anthropometric features.…”
Section: Dl-driven Hrtf Personalization and Generalizationmentioning
confidence: 99%
“…A recent overview of HRTF interpolation by PCA is given by Xie [4]. Various studies had found PCA to be effective in HRTF representation and estimation [13][14][15]. Existing PCA applications to HRTF interpolation involve non ear-aligned HRTFs.…”
Section: Introductionmentioning
confidence: 99%